Characterization of Biogas as an Alternative Fuel in Micro-Scale Combustion Technology - Sanata, Andi; Sholahuddin, Imam; Rosyadi, Ahmad Adib; Nanlohy, Hendry Y.; Nashrullah, Muhammad Dimyati; Budi Erawan, Ilyas Nugraha; Mulyadi, Santoso; Ramadhan, Mochamad Edoward (International Journal of Integrated Engineering, 2023)
This study observes the characteristics of the flame of biogas combustion in micro/meso-scale (MSC) combustion technology, namely in a cylindrical MSC with fuel variations and combustor variations with backward-facing step size (bfs) as the flame holder in the combustor as a comparison. The bfs are varied by changing the combustor's length of the inlet diameter. In contrast, the size of the outlet diameter of the combustor is always constant to obtain a continuous combustion reaction zone. Biogas, butane gas (C4H10), and a mixture of biogas-butane are used as fuel, with air as the oxidizing agent. The results showed that the type of fuel, reactant flow velocity, and equivalent ratio that occurred in the fuel variation and the bfs variation of the cylindrical MSC influenced the flame characterization. Stable flame forms in the stoichiometric to rich equal ratio area and medium to high reactant velocity area. The best characterization of biogas combustion is formed in the variation of biogas treatment by mixing butane gas (biogas-butane). One of the methods used is called with a wider flame stability limit area, more varied flame visualization variations with a more widely distributed flame mode map, and flame and combustor wall temperature higher than the characterization of biogas combustion without mixing butane gas for the possible test ranges.